1992
DOI: 10.1111/j.1756-1051.1992.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Sideritis syriaca ssp. syriaca: Glandular trichome structure and development in relation to systematics

Abstract: S. 1992. Sideriiis svriaca SSD. svriaca:Glandular trichome structure and development in relation to systematics. : Nbrd. J.Bot. 12: 31-37. Copenhagen. ISSN 0107-055X.Sideritis syriaca ssp. syriaca is a taxon with a low essential oil content. Its leaves bear glandular trichomes of two types: long hairs with a 4-celled head, a 4-celled stalk and a 4-celled foot (reported for the first time in Lamiaceae) and short hairs with a 4-celled head, a unicellular stalk and a unicellular foot. The second type is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
7

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
9
0
7
Order By: Relevance
“…Comparing our results with the literature data on Sideritis [18] [19], some considerations emerge. The only trichome types common to the Sideritis species, examined so far, are types B and C x ; indeed, S. romana lacks type-C 1 hairs [18], whereas S. syriaca subsp.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Comparing our results with the literature data on Sideritis [18] [19], some considerations emerge. The only trichome types common to the Sideritis species, examined so far, are types B and C x ; indeed, S. romana lacks type-C 1 hairs [18], whereas S. syriaca subsp.…”
mentioning
confidence: 68%
“…The only trichome types common to the Sideritis species, examined so far, are types B and C x ; indeed, S. romana lacks type-C 1 hairs [18], whereas S. syriaca subsp. syriaca [19] lacks peltate trichomes. In particular, it is noteworthy that, in this taxon, the capitate C x trichomes are distributed on leaves, whilst, in the other Lamiaceae, they are found only on the reproductive organs [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Siebert (2004) also observed that the peltate trichomes of Salvia divinorum were fully developed during the very early stage of leaf development. The capitate trichomes of Type I and Type II found on T. riparia leaves resemble the shortand long-stalked glandular trichomes found on the leaves of Sideritis syriaca (Karousou et al, 1992) and Leonotis leonurus (Ascensa˜o et al, 1995). As compared to the capitate trichomes, peltate trichomes of T. riparia have a short one-celled stalk and a large round or slightly flattened head.…”
Section: Discussionmentioning
confidence: 96%
“…Some species of Lamiaceae family have the peltate ones with a four or twelve-celled head in a single circle, which is agreement with another study (Kamatou et al, 2006). Despite their common occurrence, peltate trichomes are not observed in some Lamiaceae family (Karousou et al, 1992). Besides, some researcher reported that these trichomes were found abundantly on the vegetative organs of some species in Lamiaceae, whereas the same trichomes were rare on the reproductive organs (Serrato-Valenti et al, 1997).…”
Section: Discussionmentioning
confidence: 99%